2019
DOI: 10.15244/pjoes/93745
|View full text |Cite
|
Sign up to set email alerts
|

Production of Agri-Energy Crop Miscanthus gigantheus on Land Degraded by Power Industry: SWOT Analysis

Abstract: The Law on the Spatial Plan of the Republic of Serbia from 2010 to 2020 [1] recognizes the exploitation of mineral resources, especially in the Kolubara and Kostolac mining basins, as one of the largest sources of soil degradation and pollution. Municipals Obrenovac (thermal power plants (TPP), ash dumps), Lazarevac (surface coal mines, TPP, ash and slag disposal, coal processing), and Kostolac (TPP, open pit coal mines, ash and slag dumps) are classified as the most vulnerable areas ("hot spots") in the Repub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Remediation Contamination control -A physical, chemical or biological action to remove contaminants with the goals to reduce and manage the risks to human beings posed by contaminated sites. Alday et al 2011;Ličina et al 2017;Kalabić et al 2019;Hamidović et al 2020), but the most comprehensive research that has come from the European region is mainly from the Lusatian mining district in Germany (Rumpel et al 1998(Rumpel et al , 1999(Rumpel et al , 2000Schaaf et al 1999;Waschkies & Hüttl 1999;Zier et al 1999;Schaaf 2001Schaaf , 2003Wanner & Dunger 2001;Wiegleb & Felinks 2001;Wilden et al 2001;Schaaf & Hüttl 2006) and the Sokolov mining district in the Czech Republic (Kříbek et al 1998;Frouz et al 2001Frouz et al , 2007aFrouz et al , b, 2013Frouz & Nováková 2005;Šourková et al 2005a, b;Baldrian et al 2008;Helingerová et al 2010;Řehounková et al 2011;Bodlák et al 2012;Brom et al 2012;Heděnec et al 2017). In more recent years, an increasing number of publications related https://doi.org/10.17221/163/2020-SWR to reclamation sites have originated from China and, even more so, India.…”
Section: Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Remediation Contamination control -A physical, chemical or biological action to remove contaminants with the goals to reduce and manage the risks to human beings posed by contaminated sites. Alday et al 2011;Ličina et al 2017;Kalabić et al 2019;Hamidović et al 2020), but the most comprehensive research that has come from the European region is mainly from the Lusatian mining district in Germany (Rumpel et al 1998(Rumpel et al , 1999(Rumpel et al , 2000Schaaf et al 1999;Waschkies & Hüttl 1999;Zier et al 1999;Schaaf 2001Schaaf , 2003Wanner & Dunger 2001;Wiegleb & Felinks 2001;Wilden et al 2001;Schaaf & Hüttl 2006) and the Sokolov mining district in the Czech Republic (Kříbek et al 1998;Frouz et al 2001Frouz et al , 2007aFrouz et al , b, 2013Frouz & Nováková 2005;Šourková et al 2005a, b;Baldrian et al 2008;Helingerová et al 2010;Řehounková et al 2011;Bodlák et al 2012;Brom et al 2012;Heděnec et al 2017). In more recent years, an increasing number of publications related https://doi.org/10.17221/163/2020-SWR to reclamation sites have originated from China and, even more so, India.…”
Section: Rehabilitationmentioning
confidence: 99%
“…Studies of determining the levels of risk elements on coal reclamations were also performed by Tang et al (2018), and the results have shown that the finer the texture of the soil is, the higher the heavy metal concentrations were. Other studies have dealt with risk elements all over the world, and, in some instances, elevated or high concentrations of elements such as arsenic (As), nickel (Ni), https://doi.org/10.17221/163/2020-SWR copper (Cu), lead (Pb), chromium (Cr), cobalt (Co), zinc (Zn), iron (Fe), manganese (Mn), cadmium (Cd), and mercury (Hg) were observed (Giri et al 2013;Bragina et al 2014;Ličina et al 2017;Bandyopadhyay et al 2018;Jambhulkar & Kumar 2019;Kalabić et al 2019;Raj 2019;Hamidović et al 2020). Štrudl et al (2006), on the other hand, based on a research from 116 sampling locations, stated that risk elements did not present a threat in the Sokolov mining basin in the Czech Republic.…”
Section: Reviewmentioning
confidence: 99%
“…SWOT-analysis as one of the common and well-known tools for assessing the environment and choosing the priorities of community activities is often used for various purposes, both for internal analysis and external stakeholders. For example, this approach is relevant for assessing the feasibility and alternatives of investment in land (Remeikiene et al, 2018), the impact of the development of certain sectors of the economy on job creation in the region (Ahmed et al, 2018), the development of certain agricultural types in rural communities given the opportunities and threats to landowners and ecosystems (Kalabić et al, 2019), assessing the investment attractiveness of areas for foreign investors (Gavatiuk et al, 2020). The active use of environmental assessment tools and development priorities significantly expands the opportunities of communities to access external financial resourcesinvestment, grant and other funds available under the material and technical support programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Biogas production processes are more efficient than those for bioethanol and biodiesel. Adequate policies (political environment) are needed to correctly regulate the market for the production and distribution of electric energy through the use of biogas (Arndt, Pauw and Thurlow, 2015;Goetz, et al, 2018;Gheewala, 2013;Kalabić et al, 2019;Zonin, 2014), which is an environmentally friendly alternative to produce energy (heat and electricity).…”
Section: General Aspects About Biofuelsmentioning
confidence: 99%
“…Regarding the Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis, the elements that strengthen the position of biofuels and opportunity areas were considered for improvement according to different authors (Catron et al, 2013;Okello et al, 2014;Soimu, 2014;Paschalidou Tsatiris and Kitikidou, 2016;Phadermrod, Crowder and Willis, 2019;Georgakopoulou, 2019;Kalabić et al, 2019;Zalengera, 2014) and the interview results. This analysis was performed out considering strengths and weaknesses as current states, and opportunities and threats as future states criteria.…”
Section: Swot Analysismentioning
confidence: 99%